The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)

The Twentieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2001)

The Twenty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2002)

The Twenty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2003)

The Twenty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2005)

The Twenty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2006)

The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

The Twenty-Seventh Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2008)

The Twenty-Eighth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2009)

Strategic Plan : 2005-2006 to 2008-2009 - The English Speaking Catholic Council (ESCC) (2005)

Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Ethical Guidelines Handbook for the Catholic Laity in Apostolic Service - The English Speaking Catholic Council (ESCC) (2007)

Reasonable Accommodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Accommodements raisonnables et liberté de religion au Québec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Respect Minority and Community Rights in Any Health Care Reforms - The English Speaking Catholic Council (ESCC) (2004)

Gardez le lien avec la communauté - The English Speaking Catholic Council (ESCC) (2004)

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Report on the Proposed Ethics and Religious Culture Program - The English Speaking Catholic Council (ESCC) (2006)
We affirm the positive objectives of this program, namely: 1) To incorporate ethics and religion into public education; 2) To foster students’ capacity to know and express their moral and religious convictions within a pluralistic context; 3) To develop the capacity for meaningful dialogue about diverse moral and religious convictions; 4) To anchor this program in the distinctive cultural and religious heritage of Quebec. However, we recommend some major revisions to the program. Five interrelated areas stand out for us.

Mémoire présenté par le Conseil catholique d’expression anglaise sur les conditions de vie des aînés - The English Speaking Catholic Council (ESCC) (2007)

Public Consultation on Seniors' Living Conditions : A Social Issue That is the Responsibility of Us All Quebecers - The English Speaking Catholic Council (ESCC) (2007)
The English Speaking Catholic Council would like to congratulate the Government of Quebec for recognizing the importance of issues related to seniors and an aging population and its establishment of the post of Minister Responsible for Seniors. We also welcome the initiative of Mme Marguerite Blais, the Minister Responsible for Seniors, to hold public hearings on seniors’ living conditions in Quebec, an issue on which our community and its institutions serving the elderly have considerable experience and great concern.

Statement on Bill 21 : An Act Respecting the Laicity of the State - The English Speaking Catholic Council (ESCC) (2009)
The English Speaking Catholic Council (ESCC) was founded in 1981 with the mission to act as a catalyst, convener and facilitator of collective action for the English-speaking Catholic community of Quebec. As an organization inspired by Catholic social teaching, the Council is concerned for the common good and is apprehensive as to the implications of Bill 21 (An Act respecting the laicity of the State) for the social and civic welfare of Quebec society. In the main, the objections the Council have regarding the current legislation are similar to those we expressed in our 2013 brief on Bill 60 (Charter affirming the values of State secularism and religious neutrality and of equality between women and men, and providing a framework for accommodation requests)1 However, there are a number of critical differences between the 2013 legislation and that introduced in 2019.

Déclaration sur le projet de loi 21 : Loi sur la laïcité de l’État - The English Speaking Catholic Council (ESCC) (2009)
Le Conseil catholique d’expression anglaise a été fondé en 1981 avec la mission d'agir comme catalyseur, rassembleur et facilitateur de l'action collective pour la communauté catholique anglophone au Québec. En tant qu'organisme inspiré par l'enseignement social catholique, le Conseil se préoccupe du bien commun et s’inquiète donc des implications du projet de loi 21 (Loi sur la laïcité de l'État) pour le bien-être social et civique de la société québécoise. Pour l’essentiel, les objections du Conseil à l'égard de la législation actuelle sont semblables à celles que nous avons exprimées dans notre mémoire de 2013 sur le projet de loi 60 (Charte affirmant les valeurs de la laïcité d'État, de la neutralité religieuse et de l'égalité entre les femmes et les hommes, et fournissant un cadre pour les demandes d'accommodement).

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.